Revisions of Modular Metal-on-metal THA Have a High Risk of Early Complications. Issue 2 (February 2019) - Jennings, Jason M.; White, Samuel; Martin, J. Ryan; Yang, Charlie C.; Miner, Todd M.; Dennis, Douglas A.
Abstract: Background: The risk of early complications is high after monoblock acetabular metal-on-metal (MoM) THA revisions. However, there is a paucity of evidence regarding clinical complications after isolated head-liner exchange of modular MoM THA. Questions/purposes: The purposes of this study were (1) to describe the frequency of early complications after an isolated head-liner exchange revision of modular MoM THA; and (2) to determine whether patients who experienced complications or dislocation after head-liner exchanges had higher serum chromium (Cr) or cobalt (Co) ion levels than those who did not. Methods: A review of our institution's total joint registry retrospectively identified 53 patients who underwent 54 liner exchange revisions of a modular acetabular MoM THA. The study period was from April 2008 to April 2016 at a single tertiary care center. During this period, isolated head-liner exchanges (rather than more extensive revisions) were performed in patients if they did not have evidence of loosening of the acetabular or femoral components. Reasons for revision surgery included pain, mechanical symptoms, radiographic evidence of osteolysis, elevated serum metal ions, and MRI abnormalities with 40 of the 54 hips having pain or mechanical symptoms and 38 of 54 hips having multiple reasons for revision before surgery. Patients were excluded if they did not meet the minimum postrevision followup or had the modular liner exchange secondary to infection. All revisions were from a single manufacturer with one head-liner exchange of a MoM THA from another manufacturer excluded during the study period. The mean time from index MoM THA to modular exchange was 96 (SD ± 36) months. Because the focus of this study was early complications, we had a minimum 90-day followup duration for inclusion. Mean followup after revision was 15 months (SD ± 12); a total of 56% (30 of 54) had followup of at least 12 months' duration. Complications (dislocation, infection) and reoperations were obtained by chart review performed by individuals other than the treating physician(s). Serum metal ion levels were obtained before head-liner exchange. The median serum Cr and Co levels were 6 µg/L (range, 0-76 µg/L) and 12 µg/L (range, 0-163 µg/L), respectively. Results: Of the 54 revision THAs, 15 (28%) developed complications. Nine (17%) occurred within 90 days of the revision surgery and 11 (20%) resulted in reoperation. The most common complication was dislocation (12 of 54 [22%]) with recurrent dislocation noted in eight of these 12 patients. All patients with recurrent dislocation continued to dislocate and underwent repeat revision. Patients with dislocation had higher median serum Cr and Co ion levels than those without dislocation (Cr: 24 [range, 11-76] versus 4 [range, 0-70], p = 0.001 [95% confidence interval CI, 10-57]; Co: 41 [range, 6-163] versus 8 [range, 0-133], p = 0.016 [95% CI, 6-141]). Three (6%) of the 54 patients underwent repeat surgery for deep space infection. Conclusions: Complications and reoperations are common after modular head-liner exchange in the setting of a failed MoM THA. Our study likely underestimates the frequency of complications and revisions because the followup period in this report was relatively short. Dislocation is the most common complication and elevated serum metal ion levels may be a predictor of dislocation. These findings are concerning and surgeons should be aware of the high complication risk associated with this procedure. Level of Evidence: Level IV, therapeutic study.